CORRELATIONS OF DEOXYRIBONUCLEIC ACID METHYLATION, HISTONE ACETYLATION, AND MICRORNA‑320 WITH SORBITOL DEHYDROGENASE IN DIABETIC RETINOPATHY - AMIN, RAMZI; HILMANTO, DANY; KARTASASMITA, ARIEF S.; PERMANA, HIKMAT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Prolonged and persistent hyperglycemia in diabetes mellitus (DM) leads to a variety of vascular complications, including the retinal disorder of diabetic retinopathy (DR). The mechanism of fructose formation of sorbitol assisted by sorbitol dehydrogenase (SDH) causing the loss of pericytes in the blood vessel is affected by epigenetic work comprised of deoxyribonucleic acid (DNA) methylation, histone acetylation, and microRNA‑320. This study aimed to determine the correlation of DNA methylation, histone acetylation, and microRNA‑320 with SDH in DR. Methods: This case–control study was conducted at a tertiary general hospital from July 2014 to June 2016. Study subjects were type 2 DM patients with and without DR, over 40 years old, suffered from DM for > 10 years. DNA methylation, histone acetylation, and microRNA‑320 were examined by real‑time quantitative polymerase chain reaction, while SDH level examination was carried out by enzyme‑linked immunosorbent assay. Analyses were performed with independent t‑test, Mann–Whitney, Spearman correlation, and multiple linear regression. Results: With respect to SDH, DNA methylation showed no significant correlation so as histone acetylation, in contrary to microRNA‑320 with a very strong negative correlation (r=−0.968, P < 0.005). Conclusion: MicroRNA‑320 was correlated to SDH in a manner of protective properties against the occurrence of DR. Involvement of DNA methylation and histone acetylation was perceptible in influencing SDH enzyme despite their insignificance if they took place individually.